Therapeutic effects of herbal-medicine combined therapy for COVID-19: A systematic review and meta-analysis of randomized controlled trials - Chien, Tsai-Ju; Liu, Chia-Yu; Chang, Yuan-I; Fang, Ching-Ju; Pai, Juo-Hsiang; Wu, Yu-Xuan; Chen, Shuoh-Wen (Frontiers in Pharmacology, 2022)
Background/Aim global health to a great extent. Some countries have added on herbal medicines as a complementary treatment for combating COVID-19 due to the urgency of stopping the spread of this viral disease. However, whether these herbal medicines are effective is uncertain. This systematic review and meta-analysis aimed to evaluate the effects of add-on herbal medicine in the treatment of COVID-19. Methods A literature search was performed following the PRISMA Statement and without language restrictions. Seven databases were searched from inception through December 2021. All selected studies were randomized clinical trials (RCTs). comparing the effects of combining herbal medicine with conventional western medicine, including improvement of clinical symptoms, chest CT images, viral conversion rate, C-reactive protein (CRP) and interleukin 6. Cochrane criteria were applied to examine the methodological quality of the enrolled trials; and meta-analysis software (RevMan 5.4.1) was used for data analysis. Results In total, the data of 5417 participants from 40 trials were included in this systematic review; and 28 trials were qualified for meta-analysis. The trials had medium-to-high quality based on the modified Jadad scale. Meta-analysis showed that combining herbal medicine vs. conventional treatment in (1) coughing (1.43 95% CI:1.21, 1.71, P= 0.0001;), (2) fever (1.09 95% CI:1.00, 1.19, P= 0.06), (3) fatigue (1.21 95% CI:1.10, 1.33, P= 0.0001); (4) CT images (1.26 95% CI:1.19, 1.34, P<= 0.00001), (5) viral conversion rates (1.22 95% CI:1.06, 1.40, P= 0.005) and (6) viral conversion times (-3.72 95% CI:-6.05, -1.40, P= 0.002), (7) IL6 change: (1.97 95% CI:-0.72, 4.66, P= 0.15) and (8) CRP change (-7.92 95% CI:-11.30, -4.53, P<= 0.00001) Conclusion Add-on herbal medicine significantly reduces COVID-19 clinical symptoms, improving CT images and viral conversion rates. Reported adverse events are mild. However, for certain biases in the included studies, and the need for further study on effective components of herbal medicine. Further large trials with better randomized design are warranted to definite a more definite role of herbal medicine.